Long-Term Changes in Carotid Intima-Media Thickness among HIV-Infected Children and Young Adults. Issue 1 (January 2014) - Eckard, Allison Ross; O'Riordan, Mary Ann; Storer, Norma; McComsey, Grace A
Background: HIV-infected patients are at increased risk of cardiovascular disease (CVD). This study assessed long-term changes in carotid intima-media thickness (IMT) as a surrogate marker for CVD risk in HIV-infected children and young adults. Methods: This was a longitudinal, observational study comparing carotid IMT in HIV-infected subjects who were 2–21 years old to matched controls over 144 weeks. Results: A total of 34 HIV-infected subjects and 29 controls were included in the analyses. Among the HIV-infected group, median age was 10 years, 74% were black, and 65% were female. Overall, 91% were perinatally-infected with 82% on antiretroviral therapy and a median CD4 + T-cell count of 681 cells/mm 3 . At baseline, HIV-infected subjects had increased internal carotid artery (ICA) and common carotid artery (CCA) IMT (ICA, HIV-infected 0.90 mm versus controls 0.73 mm; P <0.01; CCA, HIV-infected 1.00 mm versus controls 0.90 mm; P =0.02). Relatively large changes in ICA and CCA IMT were seen from year to year in both groups. However, by week 144, there were no net changes in ICA or CCA IMT within the HIV-infected group. In the controls, CCA increased 0.1 mm and ICA increased 0.17 mm from baseline to week 144. ICA and CCA IMT were similar between groups by 144 weeks. Conclusions: Despite variations from year to year in carotid IMT in HIV-infected children and healthy controls, likely due to arterial growth and/or luminal diameter change, little or no net change occurred in carotid IMT over the entire 144-week study period. This suggests that only small net changes occur over time in HIV-infected children despite an increased long-term risk of CVD.